The circuit designer's companion - Williams, Tim, 1954- (Butterworth-Heinemann, 1991)
The Circuit Designer's Companion covers the theoretical aspects and practices in analogue and digital circuit design. Electronic circuit design involves designing a circuit that will fulfill its specified function and designing the same circuit so that every production model of it will fulfill its specified function, and no other undesired and unspecified function. This book is composed of nine chapters and starts with a review of the concept of grounding, wiring, and printed circuits. The subsequent chapters deal with the passive and active components of circuitry design. These topics are followed by discussions of the principles of other design components, including linear integrated circuits, digital circuits, and power supplies. The remaining chapters consider the vital role of electromagnetic compatibility in circuit design. These chapters also look into safety, design of production, testability, reliability, and thermal management of the designed circuit.